2019
DOI: 10.1159/000499565
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gap and Modulations: Auditory Temporal Resolution Deficits in Adults Who Stutter

Abstract: <b><i>Background:</i></b> Recent models of speech production suggest a link between speech production and perception. Persons with stuttering are known to have deficits in sensorimotor timing and exhibit auditory processing problems. Most of the earlier studies have focused on assessing temporal ordering in adults who stutter (AWS), but limited attempts have been made to document temporal resolution abilities in AWS. <b><i>Methods:</i></b> A group of 16 AWS and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, more recent empirical findings do not sup-port this hypothesis: If AF-based monitoring was over-sensitive in terms of timing, one would expect stronger responses to time manipulation of AF, but the opposite was found: Adults who stutter (AWS) showed weaker articulatory compensation of unexpected time-varying AF perturbations than fluent controls (Cai et al, 2014). Moreover, Devaraju et al (2020) found AWS, as compared with fluent controls, to be less sensitive to temporal fluctuations in speech rhythm.…”
Section: Distraction From Auditory Feedbackmentioning
confidence: 97%
See 1 more Smart Citation
“…However, more recent empirical findings do not sup-port this hypothesis: If AF-based monitoring was over-sensitive in terms of timing, one would expect stronger responses to time manipulation of AF, but the opposite was found: Adults who stutter (AWS) showed weaker articulatory compensation of unexpected time-varying AF perturbations than fluent controls (Cai et al, 2014). Moreover, Devaraju et al (2020) found AWS, as compared with fluent controls, to be less sensitive to temporal fluctuations in speech rhythm.…”
Section: Distraction From Auditory Feedbackmentioning
confidence: 97%
“…More important, abnormalities were found even in the processing of non-speech auditory stimuli (e.g., Arcuri, Schiefer, & Azevedo, 2017;Chang et al, 2009;Devaraju, Maruthy, & Kumar, 2020;Dietrich, Barry, & Parker, 1995;Hampton & Weber-Fox, 2009;Howell, Davis, & Williams, 2006;Kikuchi et al, 2011: Saltuklaroglu et al, 2017. The results of these studies are not well comparable because of different approaches and methods; however, some authors (Kikuchi et al, 2011(Kikuchi et al, , 2017Saltuklaroglu et al, 2017) point to impaired sensory gating during the basic processing of audi-tory input, that is, the processing of redundant input is insufficiently suppressed.…”
Section: Deficit In Auditory Processingmentioning
confidence: 99%
“…Difficulties in auditory processing abilities among individuals who stutter have been measured using behavioral and electrophysiological tests (Jansson-Verkasalo et al, 2014) [11] . Frequently used behavioral tests are; dichotic digit test (DDT) (Robb et al, 2013) [12] for sound localization and lateralization, gap in noise test (GIN) (Devaraju et al, 2019) [13] for auditory temporal discrimination and resolution, speech intelligibility perception in noise (SPIN) (Asal and Abdo, 2014) [14] for auditory closure, and pitch pattern sequence test (PPST) (Lotfi et al, 2020) [15] for temporal ordering or sequencing. Frequently used electrophysiological tests are cortical auditory evoked potentials (CAEPs) (Ismail et al, 2017) [16] and speech auditory brain stem response (sABR) (Mozaffarilegha et al, 2019) [17] .…”
Section: Introductionmentioning
confidence: 99%
“…This was interpreted in the context of the temporal sampling hypothesis ( Goswami, 2011 , 2019 ), which states that delta and theta oscillations in auditory cortex are important for prosody perception and temporal integration at the syllable rate, respectively. The temporal sampling hypothesis is also applicable to other communication disorders like stuttering, wherein individuals exhibit impaired rhythm processing ( Wieland et al, 2015 ), poor temporal resolution ( Devaraju et al, 2020 ), and aberrant neural phase coherence when planning speech utterances ( Sengupta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%